Utilizing Demonstrations in Teaching, with an Example Demonstration of Propagation via Cuttings - Isabella Damiani; Andrew C. Thoron; James C. Bunch (EDIS)
In a learning environment, it is important to provide instruction to each type of learner. This 4-page document discusses utilizing demonstrations for different types of learners and includes a sample demonstration of plant propagation. Written by Isabella Damiani, Andrew Thoron, and J. C. Bunch and published by the UF/IFAS Department of Agricultural Education and Communication, May 2018. Revised January 2021. http://edis.ifas.ufl.edu/wc306